2018
DOI: 10.1080/17436753.2018.1495896
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electrophoretic deposition copper–carbon nanotubes composite coatings in deep eutectic solvent using a Taguchi experimental design approach

Abstract: The present work discusses the electrophoretic deposition (EPD) of copper-carbon nanotubes (Cu-CNTs) composite coatings in a Deep Eutectic Solvent (DES) media, using a non-symmetric deposition process. A Taguchi experimental design is implemented in order to assess the effect of the different parameters on the microstructural characteristics of the coatings. The analysis of the design of experiments (DOE) is performed with the signal to noise (S/N) ratio and the analysis of variance. The results clearly reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Jeyarag et al 38 carried out investigations on the effect of process parameters of electrodeposited Ni-Al2O3 composite coating, and also 39 studied electrodeposited Ni-Cr composite coating using a Taguchi L27 orthogonal array approach and mathematical modelling, using robust design approach. Pech-Rodríguez et al 40 studied the electrophoretic deposition of copper-carbon nanotubes composite coatings in deep eutectic solvent using a Taguchi experimental design approach. The optimisation of microhardness of electrodeposited Co-Ag coatings using Taguchi design and ANOVA methods was carried out by Kirati et al 41…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Jeyarag et al 38 carried out investigations on the effect of process parameters of electrodeposited Ni-Al2O3 composite coating, and also 39 studied electrodeposited Ni-Cr composite coating using a Taguchi L27 orthogonal array approach and mathematical modelling, using robust design approach. Pech-Rodríguez et al 40 studied the electrophoretic deposition of copper-carbon nanotubes composite coatings in deep eutectic solvent using a Taguchi experimental design approach. The optimisation of microhardness of electrodeposited Co-Ag coatings using Taguchi design and ANOVA methods was carried out by Kirati et al 41…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Although a variety of approaches have been adopted, previous studies have primarily focused on enabling the dispersion of CNTs in general CuSO 4 aqueous solutions and rarely consider the possibility of using non-aqueous baths that allow the homogeneous dispersion of hydrophobic CNTs without any treatment or dispersants. Pech-Rodríguez et al reported the possibility of using a eutectic solvent as a plating bath for Cu/CNT composite platings; however, because eutectic solvents are ionic, they required prior functionalization of the CNTs [39].…”
Section: Introductionmentioning
confidence: 99%